Questioning the Correlation Between Incidence of Hirschsprung Disease and Indications for Rectal Biopsy - Miyano, Go; Suzuki, Takamasa; Masuda, Risa; Ito, Masaki; Iida, Hisae; Kaneko, Kotaro; Abe, Eri; Ikegami, Michiaki; Nikai, Koki; Ishii, Junya; Lane, Geoffrey J; Yamataka, Atsuyuki; et al. (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2024)
To review the indications for rectal mucosal/submucosal biopsy (RMSBx) used for diagnosing Hirschsprung's disease (HD) in pediatric patients. The medical records of all children between 1 and 15 years old assessed for chronic constipation between 2012 and 2022 were reviewed. Until the end of 2018, enema usage (E+) was a major indication for RMSBx. In 2019, laxative use for 3 months irrespective of enema use was added as an indication (L+). To determine the relevance of enema usage, L+ was subdivided by enema usage into (L+E+) and (L+E-) groups. The effect of changing the indications for RMSBx on the incidence of HD was investigated. Of 562 eligible subjects, E+ = 410, L+ = 152; demographics are similar. RMSBx rate in E+ (E+RMSBx) was 36/410 (8.8%) and in L+ (L+RMSBx) was 42/152 (27.6%;) ( < .05). For L+RMSBx, 15/42 were L+E+ and 27/42 were L+E-. HD incidence in E+RMSBx was 8/36 (22.2%; E+HD) and in L+RMSBx was 13/42 (31.0%; L+HD) ( = ns). In L+RMSBx, HD incidence in L+E+ was 5/15 (33.3%; L+E+HD) and in L+E- was 8/27 (29.6%; L+E-HD) ( = ns). Differences in daily bowel motion frequency 6 months postoperatively were not statistically significant; E+HD (1.75/d) versus L+HD (2.03/d) and L+E+HD (1.60/day) versus L+E-HD (2.31/day). Unassisted voluntary defecation was confirmed 12 months postoperatively in 7/8 (87.5%) E+HD, 11/13 (84.6%) L+HD, 4/5 (80.0%) L+E+HD, and 7/8 (87.5%) L-E-HD; differences were not significant. Laxatives were still required in 2/8 (25.0%) E+HD, 3/13 (23.1%) L+HD, in 1/5 (20.0%) in L+E+HD, and 2/8 (25.0%) L+E-HD; differences were not significant. Incidence of HD was higher in L+HD, but not significantly different suggesting that indications for RMSBx have potential to influence incidence of HD and hint that the incidence of HD could actually be higher. Further assessment of additional indications is warranted to diagnose HD with greater accuracy.